2015
DOI: 10.1186/s13018-015-0292-7
|View full text |Cite
|
Sign up to set email alerts
|

Debridement, internal fixation, and reconstruction using titanium mesh for the surgical treatment of thoracic and lumbar spinal tuberculosis via a posterior-only approach: a 4-year follow-up of 28 patients

Abstract: BackgroundThe standard recommended method for surgical treatment of spinal tuberculosis is an anterior approach for debridement and fusion combined with posterior instrumentation. However, the method has its disadvantages. The aim of this study was to analyze the effectiveness and safety of treating thoracic and lumbar spinal tuberculosis with debridement, internal fixation reconstruction, and using specially formed titanium mesh cages via a posterior-only approach.MethodsThe authors retrospectively reviewed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 31 publications
3
59
0
Order By: Relevance
“…Many studies have revealed that posterior approach is able to achieve good clinical outcome when treating spinal tuberculosis [1, 2, 6, 8, 9]. Vertebral height demands reconstruction after surgical debridement, but it is still elusive to select appropriate bone-grafting materials to restore vertebral height [1, 1013].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have revealed that posterior approach is able to achieve good clinical outcome when treating spinal tuberculosis [1, 2, 6, 8, 9]. Vertebral height demands reconstruction after surgical debridement, but it is still elusive to select appropriate bone-grafting materials to restore vertebral height [1, 1013].…”
Section: Introductionmentioning
confidence: 99%
“…). Both ends of the titanium mesh cages were filled with autologous bone with allograft or autogenous bone in the middle . Both side rods were then fixed and both sides compressed to tighten the mesh cages and bone blocks.…”
Section: Treatmentmentioning
confidence: 99%
“…As the most common form of extrapulmonary tuberculosis, spinal tuberculosis has an incidence of approximately 2-3% [1,2]. Vertebral body collapse is associated with bone destruction due to tuberculosis, which leads to kyphosis deformity, neurological damage, spinal cord compression, and even paraplegia in severe cases, thus affecting the health of the population [3].…”
Section: Introductionmentioning
confidence: 99%